Prevention of Consecuences of Social Stratification between Husband and Wife through Gender Role Harmonization - Laili ‘Izza Syahriyati (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2021)
The research describe of consequences of social stratification on husband and wife. Family structure states that the husband is the patriach and the wife below him. And than talking about efforts to prevent negative impacts from social stratification with a gender approach. This study uses empirical research by interacting directly with 20 informans, maried couples. The result of the research indicated that some of the family especially husbands were considered to have the high strata in their families. As a consecuence of social stratification between husband and wife in the family is proven that most husbands have the privilege of being served and have the full right to make decisions. Therefore, it is necessary to prevent the consecuences of social stratification in family. The pattern of husband and wife relations can be carried out according to their roles and positions, so that a harmonious, happy and comfortable family is created.